The Urgency of Humanistic Principles in Developing a Technology-Based Arabic Language Curriculum in the Digital Era - Habibah, Umi; Khoirun, Fattah; Aminudin, Aminudin; Ngantori, Ngantori (Al-Qalam Institue, 2025)
This study explores the urgency of integrating humanistic principles into the development of technology-based Arabic language curricula in the digital era. Using a qualitative library research approach, the study examines the relevance, challenges, and implications of balancing human-centered education with digital transformation. The findings reveal that humanistic principles—emphasizing empathy, self-actualization, and interpersonal connection—complement the cognitive, affective, and psychomotor goals of the curriculum. In the cognitive domain, humanistic learning fosters critical thinking and reflective understanding through supportive digital environments. In the affective domain, it sustains emotional well-being and moral sensitivity amid reduced face-to-face interaction. Meanwhile, in the psychomotor aspect, digital tools such as virtual laboratories and project-based learning promote creativity, independence, and practical engagement. The synthesis between humanistic values and digital competence creates meaningful learning experiences, ensuring that technology enhances rather than replaces humanity in education. The study concludes that digital-based education must be ethically grounded in humanistic philosophy to produce not only digitally skilled learners but also empathetic, adaptive, and morally responsible individuals.